Ethical and Safety Concerns for UAV-Assisted Data Collection for Disaster Management - Dhara, Prasenjit; Radianti, Jaziar (Proceedings of the International ISCRAM Conference, 2025)
Emergency scenarios threaten human survival and well-being, requiring proactive risk assessment, hazard identification, and swift responses. In addition to several essential services, communication systems are very much useful for information exchange and situational assessment but are often disrupted by landslides. Unmanned aerial vehicles (UAVs), with their 3D maneuverability, can be deployed to effectively restore connectivity and collect safety data during such events. Key challenges include optimizing UAV placement as base stations and designing optimized trajectories for data collection, ensuring sufficient channel gain between UAVs and users. Estimating a propagation channel map through location-based measurements offers a potential solution. However, deploying UAVs to gather information raises ethical concerns, including safety, privacy, and moral implications. Addressing these requires a technoethics framework grounded in principles like beneficence, non-maleficence, autonomy, justice, and explicability. A literature review and expert consultations can provide critical insights to navigate these challenges.